Three new species of the planthopper genus Sinonissus Wang, Shi & Bourgoin, 2018 from southwest China (Hemiptera, Fulgoromorpha, Issidae) - Chang, Zhi-Min (Zookeys, 2019)
Abstract. The diagnostic characters of the Chinese planthopper genus Sinonissus Wang, Shi & Bourgoin, 2018 are redefined. Three new species of this genus, S. daozhenensis Chang & Chen, sp. nov. (Guizhou), S. hamulatus Chang & Chen, sp. nov. (Guizhou) and S. longicaudus Chang & Chen, sp. nov. (Sichuan) are described and illustrated, and their female genitalia compared. A checklist and key to the Chinese species of Sinonissus are given.